First results of an eye lens dosimetry survey in an interventional cardiology department. (8th June 2015) - Ferrari, P; Mariotti, F; Campani, L; Castelluccio, D M; Pierotti, L; Pettinato, C; Golfieri, R; Marzocchi, A; De Palma, A
Abstract: The eye lens annual dose limit for exposed personnel to ionizing radiation has recently been revised by the ICRP—International Commission on Radiological Protection and the proposed new limit has been accepted by European legislation through the Council Directive 2013/59/EURATOM 2013. Among medical exposed personnel, the staff performing interventional cardiology are usually affected by relevant doses. For this reason a survey, employing dosemeters characterized in terms of H p (3), was performed in order to get the order of magnitude of the doses received by the eye lens, at least as a first guess. The survey showed that the annual dose limit can easily be reached if a proper radiation protection approach is not implemented.